2018
DOI: 10.31258/jes.2.2.p.33-41
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mathematical Thinking Ability with Modified MOORE Method on Learning Outcomes of Basic Mathematic II Chemical Education Students

Abstract: Developing the ability of absolute thinking is needed in mathematic class where the subject has a characteristic as a branch of science which the object of study is abstract-natured and related with a pattern of thinking. Basic mathematics is one of the courses that can develop student’s ability to think. The results acquired by the students are still not maximized; this is because the students struggle to develop their own knowledge to form concepts. Student’s activities in the learning process are only skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 1 publication
1
9
0
2
Order By: Relevance
“…School-based curriculum standards reveal that students must have a set of mathematical competencies that are manifested after the learning process occurs (Hutapea, 2019). Students' thinking skills must be developed to understand mathematics correctly (Heleni, et al, 2018). One of the goals of mathematics learning listed in the 2013 Curriculum is mathematical problem-solving.…”
mentioning
confidence: 99%
“…School-based curriculum standards reveal that students must have a set of mathematical competencies that are manifested after the learning process occurs (Hutapea, 2019). Students' thinking skills must be developed to understand mathematics correctly (Heleni, et al, 2018). One of the goals of mathematics learning listed in the 2013 Curriculum is mathematical problem-solving.…”
mentioning
confidence: 99%
“… Mathematical thinking is a mathematical process that includes five aspects, one of them is to solve mathematical problems (Heleni et al, 2018). Mathematical problem-solving ability is one of the basic abilities that must be mastered by students, this is because the problem-solving ability is considered the heart of mathematics, (Putra et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have shown that metacognition plays an essential role in problem solving as well as in the acquisition and application of skills acquired in the various fields of the discovery of the skeleton of the mathematical thinking well structured. The difficulty of students in mathematical problem solving is caused by the questions given are not present in the previous simple and easy questions the students are accustomed to (Heleni et al, 2018). In addition, according to the (Santosa et al, 2013) practicing solve math problems are early in the efforts helped overcome the difficulties students in solve math problems.…”
Section: Introductionmentioning
confidence: 99%